Unlocking the Potentials of Helium in Nigeria - Omo-Irabor, Omo; Omo-Irabor, Omoleomo (European Journal of Applied Sciences, 2021)
With the dwindling price of crude oil globally and its negative consequences on the economy and environment, there is an urgent need to diversify in the search for alternative sources of revenue for the country particularly in the Oil and Gas sector. The discovery of radiogenic helium in commercial quantity serves to augment the gross domestic product of any nation due to the various roles it plays in our everyday life; from entertainment to the medical field, where it is used for cooling superconducting magnets in medical Magnetic Resonance Imaging (MRI) scanners and Nuclear Magnetic Resonance (NMR) spectrometers to industrial applications as an agent for in maintaining controlled atmosphere and in detecting leakages. It is also useful in supersonic wind tunnels because of its stability, thermal and caloric perfect nature as well as its high speed of sound and high heat capacity ratio. Just recently, it was discovered that helium is being used to create hard drives in computers. Helium has no known substitution in cryogenic uses. It is obvious that there is a great need for the indigenous sourcing of this valued resource which is non-renewable. The discovery of large quantities of helium in Tanzania has heightened the search for this noble gas in Nigeria. This paper is therefore aimed at reviewing the generation, migration and reservoir accumulation of the gas from both biogenic and abiogenic sources.in order to support and likewise make vital contribution towards sourcing for helium in Nigeria.